Initial Report of a Phase I Study of LY2510924, Idarubicin, and Cytarabine in Relapsed/Refractory Acute Myeloid Leukemia - Boddu, Prajwal; Borthakur, Gautam; Koneru, Mythili; Huang, Xuelin; Naqvi, Kiran; Wierda, William; Bose, Prithviraj; Jabbour, Elias; Estrov, Zeev; Burger, Jan; Alvarado, Yesid; Deshmukh, April; et al. (Frontiers in Oncology, 2018)
Background: The CXCR4/SDF-1α signaling axis is critical for homing of stem cells in the bone marrow and activation of downstream pathways involved in cell proliferation and survival. In an AML model, LY2510924, a peptide antagonist of CXCR4, showed significant anti-leukemia activity. Methods: A phase I study was designed to determine the safety and toxicity profile of combination therapy of LY2510924, idarubicin and cytarabine (IA) in relapsed/refractory (R/R) AML. Patients aged 18- 70 years receiving salvage therapy (up to salvage 3) were eligible. LY2510924 is administered daily for 7 days followed by IA starting day 8. Two dose escalation levels (10 and 20 mg) were planned; up to 12 patients were to be enrolled in phase I portion. Results: Eleven patients have been enrolled with a median age of 55 (range, 19-70). Median number of prior therapies was 1 (1-3). Six pts were treated at dose-level ‘0’ (10 mg) and 5 at dose-level ‘1’ (20 mg). Only one patient experiencing a dose limiting toxicity (grade 3 rash and myelosuppression). At the starting dose-level ‘0’, three complete responses (CRs) were observed; at dose-level ‘1’, one achieved CR; the overall response rate was 36% (4 of 11 patients). By flow cytometry, 4 of 9 had ≥ 50% decrease in CXCR4 mean fluorescence intensity, indicating incomplete suppression of CXCR4-receptor occupancy. Conclusions: Combination of LY2510924 with IA is safe in R/R AML pts. Dose-escalation to a 30 mg LY2510924 dose is planned to achieve complete blockade of CXCR4 receptor occupancy, followed by expansion phase at the recommended phase 2 dose-level.